Reconceptualizing Islamic Educational Management: A Literature-Based Integration of Flipped Learning and Sustainability - Indri Indri; Mazlini Adnan (AL-ISHLAH: Jurnal Pendidikan, 2026)
The growing demand for pedagogical innovation and sustainability-oriented education has created a need to integrate modern learning models with value-based educational frameworks. In Islamic education, this challenge involves aligning technological advancements with spiritual and ethical principles. However, limited studies have explored the integration of the flipped classroom model and Education for Sustainable Development (ESD) within Islamic educational management. This study employed a qualitative approach using a systematic literature review. Relevant articles were collected from major academic databases, including Scopus, Web of Science, ERIC, and Google Scholar, based on predefined inclusion criteria. A total of 28 selected studies were analyzed using thematic synthesis to identify key concepts, patterns, and relationships among flipped learning, sustainability education, and Islamic educational principles. The findings reveal a strong conceptual synergy between the flipped classroom model and ESD. The flipped classroom supports independent learning, critical thinking, and efficient use of instructional time, while ESD provides ethical direction related to environmental, social, and economic sustainability. When integrated within Islamic educational management, these approaches align with core values such as responsibility (khalifah), balance, and holistic human development. The study proposes a conceptual framework that positions flipped learning as a pedagogical mechanism, ESD as value-oriented content, and Islamic management as the guiding philosophical structure. This integration offers a transformative approach to Islamic education by bridging technological innovation with sustainability and spirituality. It enhances student engagement, promotes holistic competencies, and supports the development of ethically responsible learners. The study highlights the need for institutional support, teacher capacity building, and empirical validation of the proposed framework.